Effect of Anthropogenic Type and Depth on Microplastic Abundance in Mahakam River Water, Samarinda City - Meicahayanti, Ika; Sari, Putri Intan Permata; Nugroho, Searphin; Rahayu, Dwi Ermawati; Ibrahim, Ibrahim (Trends in Sciences, 2023)
Mahakam is the second longest river in Indonesia and it functions as a source of raw water for drinking and other essential activities for the Samarinda people. Furthermore activities in the watershed generate solid waste such as plastic, which enters the waters and is potentially degraded into microplastics. There is a possibility that the presence of microplastics is affected by anthropogenic types along the river. Therefore, this research aims to determine the effect of anthropogenic type and river depth on the microplastic abundance in the Mahakam River. The samples were taken using an integrated approach at 3 depths, namely 0.5, 1, and 1.5 m, in 2 locations with different anthropogenic types. The sampling points include Kampung Tenun and Bukuan Villages, which represented densely populated and non-populated areas, respectively. The water collected was prepared with the following steps, which include filtration with 180 μm nylon, elimination of organic matter, density separator, and final filtration. Microplastic samples were identified based on the type, color, size, and type of polymer using a microscope and FTIR. The results show that there are 3 types of microplastics, 4 colors, and 5 size categories dominated by fiber type, black, and the smallest size, respectively. There are differences in abundance in Kampung Tenun and Bukuan Villages, namely 91 particles/L and 71 particles/L, indicating the effect of the anthropogenic type. Sampling depth also affects abundance, hence, the greater the depth, the lower the abundance value. It was also discovered that anthropogenic type and depth factors influence the identified polymer types. Nylon and nitrile polymer types were found at 2 locations and 3 sampling depths, but PVC, PETE, and PS were only found at certain locations. Furthermore, Bukuan Village, with a greater environmental factor value, has a smaller abundance than Kampung Tenun Village. HIGHLIGHTS Anthropogenic types affect the microplastic abundance in Mahakam River water Sampling depth affects the microplastic abundance in Mahakam River water Microplastics are found in Mahakam River water in 3 forms, 4 colors, and 5 types of polymers, with a size range of 180 - 5000 µm Environmental factors affect the microplastic abundance in Mahakam River water GRAPHICAL ABSTRACT